2000
DOI: 10.1046/j.1525-1470.2000.01754.x
|View full text |Cite
|
Sign up to set email alerts
|

Disseminated BCG Infection Following Bone Marrow Transplantation for X‐Linked Severe Combined Immunodeficiency

Abstract: An 8-month-old boy with X-linked severe combined immunodeficiency (XSCID) developed disseminated bacille Calmette-Guerin (BCG) infection following BCG vaccination at birth. He initially presented with an abscess at the site of BCG vaccination and was begun on three-drug antituberculous treatment (rifampicin, isoniazid, and pyrazinimide). Dissemination was subclinical prior to a human leukocyte antigen (HLA)-identical bone marrow transplant (BMT) from his sister, following which he presented with an acute eryth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 6 publications
0
16
0
Order By: Relevance
“…Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case . Sixteen of them had infection prior to HSCT, and dissemination process had occurred before transplantation as a result of inadequate immunity …”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case . Sixteen of them had infection prior to HSCT, and dissemination process had occurred before transplantation as a result of inadequate immunity …”
Section: Discussionmentioning
confidence: 50%
“…Abu Arja et al reviewed 19 reported cases of BCG infection that had been reported in post‐transplant patients with PID . Three of them had no prior evidence of infection, yet developed either local or disseminated infection following HSCT as in our case .…”
Section: Discussionmentioning
confidence: 54%
“…The first case report of acute erythroderma and recurrent BCG abscesses was presented after bone marrow transplant [32].…”
Section: Rare Complicationsmentioning
confidence: 99%
“…3,4 Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is the only treatment for SCID, but a high transplant-related mortality rate is reported in the case of disseminated BCG infection. 5 We report a case of successful management of a disseminated BCG infection in a child with a diagnosis of X-linked SCID undergoing allo-HSCT.…”
mentioning
confidence: 99%
“…In patients with T-cell defects systemic dissemination of the organism can occur, but true infection with signs and symptoms of mycobacterial disease is very rare, with an incidence rate ranging from 1 to 4.3 cases per 1 million infants vaccinated; in these cases the mortality rate is very high (60%). [4][5][6][7][8] Our patient affected with T-B+ SCID presented a localized infection at the site of inoculum and satellite lymph node, a consequence of BCG infection that became disseminated during pre-engraftment bone marrow aplasia induced by allo-HSCT conditioning regimen, despite 4 months of previous, presumptively effective anti-BCG therapy with isoniazid, rifampin and ethambutol. [9][10][11] This dissemination was finally controlled by this combination of antibiotics, with temporary addition of amikacin (3 months) and levofloxacin (6 months) 11,12 in the early postengraftment period, and immune reconstitution (despite immunosuppression for management of GvHD).…”
mentioning
confidence: 99%